Case fatality of hospitalized patients with COVID-19 infection suffering from acute respiratory distress syndrome in Germany - Sagoschen, Ingo; Keller, Karsten; Wild, Johannes; Münzel, Thomas (Viruses, 2022)
Aims: Patients suffering from viral pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are at risk of developing acute respiratory distress syndrome (ARDS). ARDS is a serious complication of COVID-19 that requires early recognition and comprehensive management. Little is known about the concomitant prevalence of both entities in Germany. Thus, we sought to analyze predictors and regional trends of case fatality in patients with COVID-19 and ARDS in Germany. Methods: We analyzed data on the characteristics, comorbidities and in-hospital outcomes for all hospitalized patients with COVID-19 and compared those with and without ARDS in Germany in 2020. Results: Overall, 176,137 hospitalized patients with confirmed COVID-19 were included in this analysis; among these, 11,594 (6.6%) suffered from ARDS. Most patients with ARDS were treated in hospitals in urban areas (n = 6485); proportion rate of mechanical ventilation was higher (45.9%) compared to those treated in hospitals of suburban (36.1%) or rural areas (32.0%). Proportion of ARDS grew exponentially with age until the sixth decade of life. Case-fatality rate was considerably higher in COVID-19 patients with ARDS compared to those without (48.3% vs. 15.8%; p < 0.001). Independent predictors of in-hospital case fatality with an OR > 3 were age ≥ 70 years, severe ARDS, severe liver disease, acute renal failure, stroke, dialysis treatment, shock and necessity of ECMO. Conclusions: The case fatality of COVID-19 patients with ARDS is dramatically high and shows relevant regional disparities. Our findings may help to draw more attention to predictors for in-hospital case fatality in patients hospitalized with COVID-19 and suffering from ARDS.
Gesehen am 27.02.2023